DINAMIKA PERKEMBANGAN DAN PENGEMBANGAN MADRASAH TSANAWIYAH DARUD DAKWAH WAL IRSYAD (MTs DDI) PALU (Perspektif Manajemen Pendidikan) - Abd. Halim Mubin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
This research discusses the dynamics of growth and development of Madrasah Tsanawiyah Darud Dakwah Wal Irsyad Palu in the review from the perspective of educational management. The research approach used is historical – sociological – pedagogical approach.. Historical - sociological - pedagogical approach intended to assess critically investigate the dynamics of growth and development of Madrasah Tsanawiyah Darud Dakwah Wal Irsyad Palu between the years 1969-2013. The results of this study indicate that the dynamic development of MTs DDI Palu from year to year since 1969 until now not experiencing significant growth. Some efforts have been made such as searching for prospective students throughout the village and the dissemination and promotion of the community around MTs DDI Palu. But the results did not show significant progress. It is influenced by several things namely: The planning function has been no integration of planning synchronization between the Regional Board of DDI Palu with MTs DDI Palu, the implementation function goes without coupled with oversight functions running simultaneously. Supposedly function execution carried out simultaneously with both internal control oversight functions performed by the head of MTs DDI Palu and external monitoring carried out by the Regional Board of DDI Palu with Madrasah Committee